PENGENALAN LONTAR USADA RARE MELALUI MEDIA LITERASI BUDAYA BERUPA KOMIK DIGITAL: - - Kadek Faldy Dwi Surastawan (ACARYA PUSTAKA, 2025)
The purpose of this study is; (1) To increase public knowledge and awareness of the importance of rare lontar usada as part of valuable cultural heritage and traditional knowledge, (2) To find out the design of cultural literacy media in the form of digital comics. This study uses a qualitative descriptive research method and the informant determination technique uses purposive sampling and snowball sampling. The author chose the research location, namely UPTD Gedong Kirtya. In this study, the researcher used observation, interview, and document study techniques to collect data in obtaining concrete data. From the results of research obtained by some, people do not know about lontar usada rare, especially those found in cities, but some people in rural areas still use the herbs written on lontar usada rare. From these results, the introduction of rare lontar usada is important to be introduced to the community because it has a value that is still relevant today as rare lontar usada contains medicinal herbs that have been used from the past to the present. In this introduction to lontar, the researcher uses digital comics, because with digital comics it is easier for readers to understand the content of the rare lontar. In the digital comic there are photos of the ingredients used as well as the efficacy of the ingredients for scattered treatment and how to use the herb